2022
DOI: 10.3390/nu14061307
|View full text |Cite
|
Sign up to set email alerts
|

Selected Organ and Endocrine Complications According to BMI and the Metabolic Category of Obesity: A Single Endocrine Center Study

Abstract: Obesity is a chronic and complex disease associated with metabolic, organ and endocrine complications. In the study, we analyzed a group of 105 patients suffering from obesity without any other previously recognized serious disorders who had been referred to a single endocrine center. The study aimed to assess the prevalence of selected organ and endocrine complications by subdividing the group, firstly according to body mass index (BMI) and secondly with regard to metabolic syndrome (MetS), pre-MetS and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…First, residual confounders could exist. Factors such as BMI status may influence the onset of hypothyroidism [ 33 ] and hormone secretion status may influence the pathogenesis of asthma [ 34 ]. Nonetheless, due to the limitations of the NHIRD, information regarding BMI, lifestyle, smoking status and precise lab data for thyroid hormones were not available.…”
Section: Discussionmentioning
confidence: 99%
“…First, residual confounders could exist. Factors such as BMI status may influence the onset of hypothyroidism [ 33 ] and hormone secretion status may influence the pathogenesis of asthma [ 34 ]. Nonetheless, due to the limitations of the NHIRD, information regarding BMI, lifestyle, smoking status and precise lab data for thyroid hormones were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Usually raised triglycerides, total and LDL cholesterol, and reduced HDL cholesterol are observed ( 8 , 37 ). However, abnormal lipid panel might result from obesity alone ( 38 ). Previous studies in subjects with CS have shown a positive correlation between FABP4 and triglycerides, and BMI ( 13 , 19 ), as observed in our cohort, while correlations with cholesterol fractions were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The link between increased cardiovascular risk and obesity can be explained by multiple mechanisms [ 166 ], such as increased incidence of hypertension [ 103 , 104 ], type II diabetes [ 109 ] and insulin resistance [ 167 ], hypercholesterolemia [ 103 ], systemic inflammation [ 168 ], endothelial dysfunction [ 169 ] and increased platelet aggregability [ 161 ].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%